Minat Baca Siswa SMP: Faktor Latar Belakang Ekonomi dan Pendidikan Keluarga (Middle School Students Reading Interests: Factors of Economic Background and Family Education) - Nurhaliza Nurhaliza; Usman Usman; Sultan Sultan (Indonesian Language Education and Literature, 2022)
This study aims to analyze students' reading interests based on economic background and family education. The population of this study was 203 students of SMP Negeri 3 Tarowang, Jeneponto, South Sulawesi. Data were collected through questionnaires and documentation. Data were analyzed by descriptive and inferential statistics. The results showed that (1) students' reading interests based on family economic background and family educational background were in the moderate category, (2) there were significant differences in students' reading interests based on family economic background, and (3) there were significant differences in students' reading interest. based on family educational background. This finding indicates that economic factors and family background have a relationship with the level of students' reading interest.Penelitian ini bertujuan unuk menganalisis minat baca siswa berdasarkan latar belakang ekonomi dan pendidikan keluarga. Populasi penelitian ini adalah 203 siswa SMP Negeri 3 Tarowang, Jeneponto, Sulawesi Selatan. Data dikumpulkan melalui kuesioner dan dokumentasi. Data dianalisis dengan statistik deskriptif dan inferensial. Hasil penelitian menunjukkan bahwa (1) minat baca siswa berdasarkan latar belakang ekonomi keluarga dan latar belakang pendidikan keluarga berada pada kategori sedang, (2) terdapat perbedaan signifikan minat baca siswa berdasarkan latar belakang ekonomi keluarga, dan (3) terdapat perbedaan signifikan minat baca siswa berdasarkan latar belakang pendidikan keluarga. Temuan ini mengindikasikan bahwa faktor ekonomi dan latar belakang keluarga memiliki hubungan dengan tingkat minat baca siswa.